2013
DOI: 10.1159/000355148
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Systemic Inflammation-Based Prognostic Scores in Patients on Regular Hemodialysis

Abstract: Background/Aims: Systemic inflammation-based prognostic scores have prognostic power in patients with cancer, independently of tumor stage and site. Although inflammatory status is associated with mortality in hemodialysis (HD) patients, it remains to be determined as to whether these composite scores are useful in predicting clinical outcomes. Methods: We calculated the 6 prognostic scores [Glasgow prognostic score (GPS), modified GPS (mGPS), neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
6
30
0
1
Order By: Relevance
“…Moreover, Harrell's concordance index highlighted that GPS was superior to others in terms of discriminating good from poor. These results were kept in line with the work of Akihiko Kato, Proctor and Pan Q [24,30,31].…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, Harrell's concordance index highlighted that GPS was superior to others in terms of discriminating good from poor. These results were kept in line with the work of Akihiko Kato, Proctor and Pan Q [24,30,31].…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, Harrell's concordance index highlighted that GPS was superior to others in terms of discriminating good from poor. These results were kept in line with the work of Akihiko Kato, Proctor and Pan Q [24,30,31].…”
Section: Discussionsupporting
confidence: 75%
“…In a number of studies, GPS scores were shown to be instrumental in making informed decisions on whether to proceed with antitumor chemotherapy in frail patients [22], in predicting clinical outcomes of hemodyalisis [23] and in both resectable and metastatic cancers [reviewed in 24]. In our study, the inflammatory GPS scores were not useful as predictors of multimorbidity, as only small percentages of each cohort had GPS above zero.…”
Section: Discussionmentioning
confidence: 59%